Review Of the Issue of Faith (Iman) In the Works of Hakim Tirmidhi - Zafar Fakhriddinov (Zien Journals, 2022)
It is not known whether Hakim Tirmidhi wrote a work in which he reflected his sectarian and doctrinal views separately. However, there are records in the sources about his treatises being written as a rebuttal to various sects. The Egyptian scholar Muhammad Juyushi, who has studied the legacy of the scholar in detail, also draws attention to this issue and points out that although al-Hakim al-Tirmidhi did not write an independent work on Kalam, the author's denials to the various sects from the point of view of the Ahl as-Sunnah reflects on some of the shortcomings of the Rafidhis' beliefs, such as "ar-Radd alar-Rafidha" and "ar-Radd alal-Muattila," which were written as a refutation of the Mu'attila sect
Keywords: Hakim Tirmidhi; Egyptian scholar